
3个回答
展开全部
|ab-2|与|b-1|互为相反数.
所以ab-2=0,b-1=0
a=2,b=1
原式=1/(1x2)+1/(2x3)+1/(3x4)+...+1/(2010x2011)
=1-1/2+1/2-1/3+1/3-1/4+...+1/2010-1/2011
=1-1/2011
=2010/2011
所以ab-2=0,b-1=0
a=2,b=1
原式=1/(1x2)+1/(2x3)+1/(3x4)+...+1/(2010x2011)
=1-1/2+1/2-1/3+1/3-1/4+...+1/2010-1/2011
=1-1/2011
=2010/2011
展开全部
|ab-2|与|b-1|互为相反数
ab-2=0
b-1=0
a=2
b=1
1/ab+1/(a+1)(b+1)+1/(a+2)(b+2)+...+1/(a+2009)(b+2009)
=1/2x1+1/3x2+...+1/2011x2010
=1-1/2+1/2-1/3+...+1/2010-1/2011
=1-1/2011
=2010/2011
ab-2=0
b-1=0
a=2
b=1
1/ab+1/(a+1)(b+1)+1/(a+2)(b+2)+...+1/(a+2009)(b+2009)
=1/2x1+1/3x2+...+1/2011x2010
=1-1/2+1/2-1/3+...+1/2010-1/2011
=1-1/2011
=2010/2011
展开全部
|ab-2|与|b-1|互为相反数说明|ab-2|=0 |b-1|=0
ab=2 b=1 a=2
1/ab+1/(a+1)(b+1)+1/(a+2)(b+2)+...+1/(a+2009)(b+2009)
=1/2+1/2×3+1/3×4+.....+1/2010×2011
=1-1/2+1/2-1/3+1/3-1/4+....+1/2010-1/2011
=1-1/2011
=2010/2011
ab=2 b=1 a=2
1/ab+1/(a+1)(b+1)+1/(a+2)(b+2)+...+1/(a+2009)(b+2009)
=1/2+1/2×3+1/3×4+.....+1/2010×2011
=1-1/2+1/2-1/3+1/3-1/4+....+1/2010-1/2011
=1-1/2011
=2010/2011
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询